Acceptability of medical male circumcision among uncircumcised young men at Mansa College of Education, Zambia : influence of perceptions about effects on male sexuality - Mlewa, Andrew Josephat (Stellenbosch : Stellenbosch University, 2013)
Thesis (MPhil)--Stellenbosch University, 2013.